An Uphill Battle: Nashville's Fight for Affordable Housing - Johnson, Stephanie. (2018)
Abstract: Nashville, Tennessee adopted an inclusionary zoning ordinance in September 2016 that aims to incentivize affordable housing creation by requesting that new developments that contain five or more units or use public resources or property shall set aside a percentage of their units for affordable housing, so long as adequate financial incentives are available from the City to subsidize these units. The ordinance was created as a direct result of the rapid gentrification and displacement that long-term residents have been experiencing since development skyrocketed in Nashville after 2010. In April 2017, The Beacon Center of Tennessee filed a suit on behalf of the Homebuilders Association of Middle Tennessee against the City of Nashville, claiming that Nashville's inclusionary zoning ordinance is illegal and unconstitutional because it violates state law and the Fifth Amendment's Takings Clause. Although Nashville was able to get the Beacon Center of Tennessee's suit against it dismissed, the state of Tennessee stepped in and passed bill SB 0363, in March 2018, that nullified Nashville's inclusionary zoning ordinance. This thesis gives an overview of inclusionary zoning jurisprudence and assesses the legality of Nashville's policy through inclusionary zoning as a valid land use regulation adopted to ensure a proper balance of housing within a community and inclusionary zoning as an exaction. It also highlights the state government versus local government political barriers that Nashville's ordinance faced during its short-lived existence.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Jonathan Witten.; Committee: Barbara Parmenter.; Keyword: Urban planning.